Akad Kerjasama di Bidang Pertanian: Akad Muzara’ah dan Musaqat - Nadya Aziz, Salfa Salsabila; Nisa', Iftita Zahrotun; Pratanti, Putri Dwi; Nur Aini, Intan; Tsabita, Rifda; Aliyah, Ni'matul; Kurniawan, Taufiq (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2025)
This study aims to analyze the concept of cooperation contracts in the agricultural sector from an Islamic economic perspective through two main forms, namely muzara'ah and musaqat contracts, and examine their legal basis and implementation in agricultural practices in society. In this study, we use a descriptive qualitative method with a library research approach, which involves analysis of classical literature (fiqh muamalah) and modern (journals and Islamic economic regulations). The results show that the muzara'ah contract is a form of cooperation between landowners and cultivators where agricultural products are divided based on an agreement, while the musaqat contract is a collaboration in managing crops that have already grown, and cultivators are obliged to be responsible for maintaining the plants until harvest time. Both have a legal basis in the Qur'an, Hadith, and the consensus of scholars, which emphasize the importance of the principles of justice, willingness, and benefit in economic cooperation. The implementation of these contracts in several agricultural regions in Indonesia shows that the muzara'ah and musaqat models are still relevant as equitable cooperation systems, especially in increasing the productivity and welfare of smallholder farmers. This research concludes that the implementation of sharia agricultural contracts can be an alternative solution in realizing an economy based on justice, blessings, and sustainability. Strengthening regulations, education, and mentoring institutions are needed so that the practice of these contracts can be optimally implemented in the national agricultural system.